PENGARUH AKSESIBILITAS, FASILITAS DAN BIAYA TIKET MASUK, TERHADAP KUNJUNGAN WISATAWAN KE LOKASI WISATA PANTAI DI PULAU AMBON PROPINSI MALUKU - Selvenco Frans Tuasuun; Teddy Christianto Leasiwal; Fransisca Soselissa; Febriyano Saptenoo (Jurnal Cita Ekonomika, 2017)
This research was carried out on February 1 until February 30, 2017, located on Ambon Island, Ambon City Region and Central Maluku Regency. aims to find out the background of tourist visits on various beach tourism objects on the island of Ambon, which relate to the factors of accessibility, facilities and entrance fee. The benefits of this writing are as study material and as a suggestion for the development of tourism in Ambon City, Maluku Province. Based on the results of the study, it is known that there are 10 famous and popular beach tourism areas on the island of Ambon, including beaches: Natsepa, Natsepa 2, Sopapei, Lawena, Tihulesi, Pasir Putih, Namalatu, Santai beach, Lubang Buaya, and Hunimua. Community accessibility to tourist sites above is quite high, and can be accessed from several departments, such as via Jembatan Merah Putih, Pasoo, Soya. liang - Morela, Alang-Wakasihu or via Hunut or Ambon City terminal to various areas on Ambon Island. Facilities and facilities at tourist sites are generally not complete and uneven and are still limited in number. Regression analysis of the effect of accessibility, facilities and entrance ticket costs for visitors / tourists is shown by the regression equation: Y = 41.1 - 4.36 X1 - 1.09 X2 + 0.715 X3, R value = 81.7% and R2 = 72.6 indicates a relationship closely and variable X affects the Y variable, and the hypothesis with the Ha variance test is received at a 95% confidence level.